(untitled) (CIPEEX, 2025)
The spread of bacteria from the oral environment is directly linked to cardiovascular diseases. Conditions such as bacterial endocarditis, atherosclerosis, and even cerebrovascular accidents have been associated with poor oral health. Despite this, there is ongoing debate about whether oral care can improve survival rates in patients undergoing thoracic surgery. Therefore, the aim of this study was to conduct a literature review to investigate whether oral care can indeed influence the survival of patients undergoing thoracic surgery. The PubMed, LILACS, and SciELO databases were searched using the following strategy: (("thoracic surgery") OR ("lung surgery") OR ("heart transplant") OR ("heart valve") OR ("lung transplant")) AND ("oral health" OR "oral treatment" OR "oral management"). Both clinical and observational studies were considered for analysis. Thirteen studies were selected for full-text review, and ultimately, seven articles were included for data extraction. Most studies focused on patients undergoing heart valve surgery. The results indicated a reduction in postoperative pneumonia and infection foci. However, only one study assessed survival, and after a six-month follow-up, it found no significant difference in survival rates between patients who underwent heart valve replacement surgery with or without dental treatment. Although the relationship between oral health and conditions such as endocarditis and pneumonia is well established, the literature lacks quantitative data on the survival rates of patients undergoing thoracic surgery who are monitored by a dental team.